2009
DOI: 10.1021/cn900029p
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-Associated Glycoprotein (MAG) Protects Neurons from Acute Toxicity Using a Ganglioside-Dependent Mechanism

Abstract: Myelin-associated glycoprotein (MAG), a protein expressed on the innermost wrap of myelin, contributes to long-term axon stability as evidenced by progressive axon degeneration in Mag-null mice. Recently, MAG was also found to protect axons from acute toxic insults. In the current study, rat dorsal root ganglion neurons were cultured on control substrata and substrata adsorbed with myelin proteins. Neurons on myelin-adsorbed surfaces were resistant to acute degeneration of neurites induced by vincristine, a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Membrane models of other mammalian organs are currently ripe for MD simulations, such as peripheral myelin sheath (PMS) membranes. These membranes contain glycolipids such as GalCer that constitute 10% of lipids in the PMS (Svennerholm et al, 1992) and more complex gangliosides that are important to membrane function (Mehta et al, 2010;Svennerholm et al, 1994). These glycolipids also exist in many different biological membranes (R贸g, 2014), but the quantity and quality of simulations with gylcolipids have been limited and this area is ripe for further study and potential force field development.…”
Section: Modeling Lipid Diversitymentioning
confidence: 99%
“…Membrane models of other mammalian organs are currently ripe for MD simulations, such as peripheral myelin sheath (PMS) membranes. These membranes contain glycolipids such as GalCer that constitute 10% of lipids in the PMS (Svennerholm et al, 1992) and more complex gangliosides that are important to membrane function (Mehta et al, 2010;Svennerholm et al, 1994). These glycolipids also exist in many different biological membranes (R贸g, 2014), but the quantity and quality of simulations with gylcolipids have been limited and this area is ripe for further study and potential force field development.…”
Section: Modeling Lipid Diversitymentioning
confidence: 99%
“…ROCK activation enhances phosphorylation of myosin light-chain phosphatase, which is a key regulator in cytoskeletal rearrangement (Brown and Bridgman, 2004). ROCK inhibitor Y-27632 can inhibit the activity of ROCK-1 and ROCK-2 (Ishizaki et al, 1996;Mehta et al, 2010) and promote axon growth (Lingor et al, 2008;Watanabe, 2010). It has been shown that crosstalk exists between hypoxia inducible factor-1 (HIF-1) and ROCK pathways in neuronal differentiation of mesenchymal stem cells, neurospheres and in PC12 neurite outgrowth (Pacary et al, 2007), and EPO is one of the major target genes of HIF-1, therefore, EPO and RhoA/ROCK pathway may also participate in the crosstalk.…”
Section: Introductionmentioning
confidence: 99%
“…By influencing membrane properties and/or by direct interaction with membrane proteins, gangliosides modulate the activity of many tyrosine kinase (25-28) and neurotransmitter receptors (29), ion channels (30, 31), and downstream cell signaling pathways. In addition, gangliosides regulate axon-myelin communication and the maintenance of myelinated axons in the adult central and peripheral nervous systems (32)(33)(34).Consistent with the pivotal role of gangliosides in the nervous system and in cell signaling, defects in their biosynthetic pathway lead to a severe infantile neurodegenerative disorder characterized by progressive brain atrophy, chorea, and epilepsy (35), symptoms that are also common to the juvenile form of HD (36).We hypothesized that in HD, decreased GM1 levels contribute to neuronal dysfunction and disease pathogenesis. Supporting this hypothesis, we demonstrated that restoring normal GM1 levels in an HD neural cell line stimulates the activation of prosurvival cell signaling pathways and provides protection from apoptosis.…”
mentioning
confidence: 99%
“…By influencing membrane properties and/or by direct interaction with membrane proteins, gangliosides modulate the activity of many tyrosine kinase (25)(26)(27)(28) and neurotransmitter receptors (29), ion channels (30,31), and downstream cell signaling pathways. In addition, gangliosides regulate axon-myelin communication and the maintenance of myelinated axons in the adult central and peripheral nervous systems (32)(33)(34).…”
mentioning
confidence: 99%